2021
DOI: 10.1094/phyto-06-20-0237-r
|View full text |Cite
|
Sign up to set email alerts
|

Two Tomato (Solanum lycopersicum) Thaumatin-Like Protein Genes Confer Enhanced Resistance to Late Blight (Phytophthora infestans)

Abstract: Late blight (caused by Phytophthora infestans) poses a serious threat to tomato production, but the number of late blight resistance genes isolated from tomato is limited, making resistance gene mining a high research priority. In this study, highly resistant CLN2037E and susceptible No.5 tomato inbred lines were used to identify late blight resistance genes. Using transcriptome sequencing, we discovered 36 differentially expressed genes (DEGs), including 21 nucleotide binding site-leucine-rich repeat (NBS-LRR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 37 publications
1
6
0
Order By: Relevance
“…POD, SOD, and APX activities were similar to those during bacterial infection, whereas CAT activity increased. Although the RT-qPCR results indicated that SITLP6 transcript levels were higher than those of SITLP5 , SITLP5 provided slightly more resistance than SITLP6 according to the symptom score, which is consistent with previous studies [ 18 ]. This may be due to higher β-1,3-GA activity in plants overexpressing SITLP5 than in those overexpressing SITLP6 .…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…POD, SOD, and APX activities were similar to those during bacterial infection, whereas CAT activity increased. Although the RT-qPCR results indicated that SITLP6 transcript levels were higher than those of SITLP5 , SITLP5 provided slightly more resistance than SITLP6 according to the symptom score, which is consistent with previous studies [ 18 ]. This may be due to higher β-1,3-GA activity in plants overexpressing SITLP5 than in those overexpressing SITLP6 .…”
Section: Discussionsupporting
confidence: 91%
“…The cluster contained six genes, five of which were TLP genes, including Solyc08g080660 and Solyc08g080670 , referred to as SlTLP5 and SlTLP6 , respectively. The overexpression and knockout of SlTLP5 and SlTLP6 corresponded to an increase and decrease in resistance to late blight, respectively [ 18 ]. The role of SlTLP5 and SlTLP6 in the defense signal transduction of tomato plants after infection with five soil-borne diseases was illustrated in our study.…”
Section: Introductionmentioning
confidence: 99%
“…A recent study showed that 19 classes of PR proteins can be distinguished based on structural similarity and functional activity [ 1 , 4 ], of which, thaumatin-like proteins (TLPs)—the homologies of sweet-tasting thaumatin isolated from the plant Thaumatococcus daniellii —belong to the PR-5 family [ 5 , 6 ]. Growing evidence shows that TLPs are involved in resistance to a variety of fungal diseases in many species, such as Gossypium hirsutum [ 7 ], Gossypium barbadense [ 8 ], Solanum lycopersicum [ 4 , 9 ], Phyllostachys edulis [ 10 ], Ganoderma lingzhi [ 11 ], Triticum aestivum L. [ 12 , 13 ], Carya cathayensis [ 14 ], Fragaria ananassa [ 15 ], Allium sativum L. [ 16 ], Pinus radiata [ 17 ], Lentinula edodes [ 18 ], Camellia sinensis [ 19 ], Cucumis melo L. [ 20 ], Avena nuda [ 5 ], Musa acuminate [ 21 ], Manihot esculenta [ 22 ], Vitis amurensis [ 23 ], Populus szechuanica [ 24 ], Camellia sinensis [ 25 ], Piper colubrinum [ 26 ], Cynanchum komarovii [ 27 ], Castanea sativa [ 28 ], Actinidia chinensis [ 29 ], and Lyophyllum shimeji [ 30 ].…”
Section: Introductionmentioning
confidence: 99%
“…TLP not only plays a critical role in the stress response but also is considered an important antimicrobial. Transcriptome sequencing of highly resistant and susceptible tomato ( Solanum lycopersicum ) varieties identified TLP as a candidate gene for resistance against late blight ( 19 ). TLP expression is induced during the wheat defense response to leaf rust attack and increases antifungal activity against Puccinia triticina ( 10 ).…”
Section: Introductionmentioning
confidence: 99%